Meta Verified Trends in Indonesia Related to Brand’s Endorsement Decisions - Putri, Vega Karina Andira; Dinansyah, Fakhriy (Universitas Dian Nuswantoro, 2024)
In June 2023, Meta Verified has been available and can be purchased in Indonesia. Meta Verified is a service that allows all Instagram and Facebook users to get a blue tick and several other benefits the company offers. The interest of Instagram users in subscribing to this service is immense because a blue tick accompanying the account name is considered to strengthen an individual's profile. The blue tick is believed to support the personal branding built by someone on Instagram to become more credible. So far, brands have a preference for choosing accounts with a blue tick because they are synonymous with their credibility in the eyes of the public. Aditya's research in 2021 shows that the source's credibility increases awareness of the company and can determine the attitude of Indonesian consumers towards a brand advertisement. The presence of Meta Verified, which now allows all users to have a blue tick without showing credibility, is the background to the paper entitled